Keep Your Litter in the Loop: Predicting Generation Z’s Intention to Recycle Single-use Plastic Waste - Herabadi, Astrid Gisela; Bella, Elsa S; Adishesa, Syanesti; Nugroho, Wahyu C (Psychological Research on Urban Society, 2023)
The introduction of single-use plastic into modern daily life has created an alarming number of plastic-waste in Indonesia. Government policies and social movements efforts to reduce and manage single-use plastic waste may not be enough. It is therefore important to study the factors related to the inclination of individual citizens to participate in the recycling effort, which is unfortunately still quite low. This study implements the Theory of Planned Behaviour to measure the predictiveness of the antecedent factors; attitude toward recycling single-use plastic, subjective norms, and perceived behavioural control; on the intention to recycle single-use plastic among Generation Z in Jabodetabek. A number of 301 participants were selected through convenience sampling method; then the structural equation modelling was performed using Jamovi to study model fit and causal relationship among the factors. The proposed structural model demonstrated good model fit. The result shows that attitude was the strongest predictor of intention; followed by perceived behavioural control which was also an important predictor of intention at a slightly lesser degree. In contrast, subjective norm was a weak direct predictor of intention, it only contributes significantly to intention via the mediation of attitude toward recycling single-use plastic.